Molecular data suggest that Heteromys irroratus bulleri should be recognized as a species-level taxon - Gutiérrez-Costa, Maria A.; González-Cózatl, Francisco X.; Ramírez-Martínez, María Magdalena; Iñiguez-Dávalos, Luis Ignacio; Rogers, Duke S. (THERYA, 2021)
Recent collecting surveys in the Sierra de Manantlán Biosphere Reserve, Jalisco (México), uncovered the existence of a new population of the Mexican spiny pocket mouse, Heteromys irroratus. Because the subspecies H. i. bulleri and H. i. jaliscensis occur nearby, our objective was to properly determine the taxonomic identity of the novel sample. Also, we evaluate its distinctiveness, both in terms of genetic divergence and phylogenetic placement, relative to other members of H. irroratus. Preliminary, we compared external and cranial measurements of recently collected individuals to those reported for representatives of the subspecies of H. irroratus occurring close by. In addition, we examined levels of genetic differentiation and phylogenetic relationships, based on sequence data of the Cytochrome b, among this population and other members of H. irroratus, including an individual from Sierra de Juanacatlán, Jalisco, the type locality of H. i. bulleri. Phylogenetic relationships were estimated using Maximum Likelihood and Bayesian Inference methods and levels of genetic divergence were assessed employing Kimura-2-parameters genetic distances. Samples from Sierra de Manantlán and Sierra de Juanacatlán were grouped together in a well-supported haplogroup and genetic distances between them were lower than < 1.02 %. Our phylogenetic hypothesis shows that H. i. bulleri represents the sister group to all other samples of H. irroratus but that, genetically, is a very divergent lineage. Distances values between H. i. bulleri to any of the other groups were > 10.05 %. Comparison of external and cranial measurements showed that, in average, individuals from Sierra de Manantlán are larger than those of H. i. jaliscensis, but more similar in size to H. i. bulleri. Our results show that the new population of the Mexican spiny pocket mouse from Sierra de Manantlán belongs to H. i. bulleri. In addition, the phylogenetic separation and the high levels of genetic divergence of H. i. bulleri, relative to other members of H. irroratus, suggest that the first should be recognized as a species-level taxon. Considering the scarce collecting records of H. i. bulleri and the known area of occurrence, that is very restricted, this taxon may warrant special conservation status.